Dose-Dependent and Subset-Specific Regulation of Midbrain Dopaminergic Neuron Differentiation by LEF1-Mediated WNT1/b-Catenin Signaling - Nouri, Parivash; Götz, Sebastian; Rauser, Benedict; Irmler, Martin; Peng, Changgeng; Trümbach, Dietrich; Kempny, Christian; Lechermeier, Carina G.; Bryniok, Agnes; Dlugos, Andrea; Euchner, Ellen; Beckers, Johannes; et al. (Frontiers in Cell and Developmental Biology, 2020)
The mesodiencephalic dopaminergic (mdDA) neurons, including the nigrostriatal subset that preferentially degenerates in Parkinson’s Disease (PD), strongly depend on an accurately balanced WNT1/b-catenin signaling pathway during their development. Loss of this pathway abolishes the generation of these neurons, whereas excessive WNT1/b-catenin signaling prevents their correct differentiation. The identity of the cells responding to this pathway in the developing mammalian ventral midbrain (VM) as well as the precise progression of WNT/b-catenin action in these cells are still unknown. We show that strong WNT/b-catenin signaling inhibits the differentiation of WNT/b-catenin-responding mdDA progenitors into PITX3+ and TH+ mdDA neurons by repressing the Pitx3 gene in mice. This effect is mediated by RSPO2, a WNT/b-catenin agonist, and LEF1, an essential nuclear effector of the WNT/b-catenin pathway, via conserved LEF1/TCF binding sites in the Pitx3 promoter. LEF1 expression is restricted to a caudolateral mdDA progenitor subset that preferentially responds to WNT/b-catenin signaling and gives rise to a fraction of all mdDA neurons. Our data indicate that an attenuation of WNT/b-catenin signaling in mdDA progenitors is essential for their correct differentiation into specific mdDA neuron subsets. This is an important consideration for stem cell-based regenerative therapies and in vitro models of neuropsychiatric diseases.